Unexpected diversity of Hyboserica chafers in South African forest remnants: cladistic analysis, new species and the new genus Leoserica (Coleoptera: Scarabaeidae: Melolonthinae). Issue 4 (27th April 2019) - Fabrizi, Silvia; Eberle, Jonas; Ahrens, Dirk
Abstract: A taxonomic revision of Hyboserica uncovers an unexpected diversity of species from Southern African forest remnants. The work results in the description of a new genus, Leoserica gen. nov., a new combination, a new synonymy and 32 new species are described. The lectotypes of Serica capensis and Triodonta caffra are designated. The habitus and male genitalia of all revised species are illustrated. A species distribution map and an identification key to the species are provided. Phylogenetic analysis reveals a deep split into one very diverse eastern clade that is distributed north to Zimbabwe, and one western clade that is restricted to the fynbos of the Cape Region.